Stabilitas Emulsi dan Sensori Mayones Campuran Minyak Abdomen Ikan Patin dan Minyak Sawit Merah dengan Penambahan HPMC SS12 Sebagai Penstabil - Dewi Fortuna Ayu; Tiara Septiani Lumban Gaol; Andarini Diharmi (Agricultural Faculty, 2020)
The purpose of this research was to determine the effect of HPMC SS12 concentration on emulsion stability and sensory quality of mayonnaise made from patin and red palm mixture oil. This study used a Completely Randomized Design (CRD) with five treatments and three replications. The treatments performed were P0 (without addition of HPMC SS12), P1 (addition of 2% HPMC SS12), P2 (addition of 3% HPMC SS12), P3 (addition of 4% HPMC SS12), and P4 (addition of 5% HPMC SS12). Data were statistically analyzed using analysis of variance (ANOVA) and then continued with Duncan`s New Multiple Range Test (DNMRT) at 5% level. Results of the research showed that the addition of HPMC SS12 significantly affected viscosity, degree of acidity (pH), emulsion stability, and sensory test of the mayonnaise thickness, but did not significantly affect moisture content, sensory test of the mayonnaise color and flavour. The best treatment was P3 (addition of 4% HPMC SS12) which had 4.53 degree of acidity (pH), 16109.33 cP viscosity, 29.78% moisture content, 72.33% emulsion stability on the 1st day, and 71.33% emulsion stability on the 15th day. Result of the descriptive test on the mayonnaise were orange somewhat yellow color, slightly rancid in aroma, and thick texture. Result of the hedonic test on overall of the mayonnaise was rather preferred by panelists.